Platform work, social protection and flexicurity in Denmark. (22nd October 2021) - Jacqueson, Catherine
Abstract: Are online platform "workers" in Denmark effectively and adequately protected against social and labour market risks? This article discusses this fundamental issue in the context of the Danish labour market, which is known for having high levels of job insecurity but a rather generous social security system. The article finds that the Danish statutory social security system provides a necessary cushion against risk, but also identifies gaps in protection, which brings into question the system's effective coverage and the adequacy of benefits. Abstract : Les «travailleurs» de plateformes en ligne bénéficient‐ils d'un accès effectif à une protection adéquate contre les risques sociaux et les risques liés au marché du travail? L'article tente de répondre à cette question centrale dans le contexte du marché du travail danois, où une forte insécurité de l'emploi coexiste avec un système de protection sociale relativement généreux. Nous constatons que le système légal de sécurité sociale fournit une protection contre les risques mais présente des lacunes qui remettent en cause sa capacité à offrir une couverture effective et des prestations adéquates. Abstract : ¿Tienen los trabajadores de las plataformas en línea de Dinamarca una protección efectiva y adecuada contra los riesgos sociales y del mercado de trabajo? En este artículo se examina esta cuestión fundamental en el contexto del mercado de trabajo danés, conocido por su alto grado de inseguridad laboral, pero que cuenta con un sistema de seguridad social bastante generoso. En el artículo se llega a la conclusión de que el régimen de seguridad social obligatorio de Dinamarca proporciona la protección necesaria contra los riesgos, pero también se señalan deficiencias en dicha protección, lo que pone en entredicho la efectividad de la cobertura del sistema y la idoneidad de los beneficios. Abstract : Sind die „Arbeitnehmer"von Online‐Plattformen wirksam und angemessen gegen soziale Risiken und gegen Arbeitsmarktrisiken geschützt? Der Artikel untersucht diese grundlegende Frage vor dem Hintergrund des dänischen Arbeitsmarkts, der dafür bekannt ist, dass die Arbeitsplatzunsicherheit hoch, das System der sozialen Sicherheit jedoch eher großzügig ist. Die Autorin kommt zum Schluss, dass das gesetzliche System der sozialen Sicherheit Dänemarks eine notwendige Abfederung gegen Risiken bietet, aber auch Schutzlücken aufweist, was die Deckungswirksamkeit und die Leistungsangemessenheit des Systems in Frage stellt. Abstract : В достаточной ли степени защищены «работники» онлайн‐платформ в Дании от социальных рисков и рисков, связанных с рынком труда? Этот фундаментальный вопрос рассматривается в статье с позиций датского рынка труда, который известен высоким уровнем нестабильности занятости, но при этом достаточно щедрой системой социального обеспечения. В статье отмечается, что государственная система социального обеспечения в Дании предоставляет необходимую защиту от рисков, и вскрываются пробелы, которые ставят под сомнение фактический охват системы и достаточность пособий. Abstract : 丹麦的在线平台是否充分有效地保障了社会和劳动力市场风险?讨论这一基本问题的背景是丹麦劳动力市场, 以工作高度不稳定但社会保障体系相当充裕而闻名。文章发现, 丹麦的法定社会保障体系为风险提供了必要缓冲, 但也发现了保护缺口, 使该体系覆盖的有效性和待遇的充足性受到了质疑。 Abstract : هل يحظى العاملون في المنصات الإلكترونية في الدانمرك على الحماية الفعالية والملائمة ضد المخاطر الاجتماعية ومخاطر سوق العمل؟ يناقش هذا المقال هذه المسألة الأساسية في سياق سوق العمل الدانمركي المعروف بمستويات مرتفعة من انعدام الأمن الوظيفي ورغم ذلك معروف بنظام ضمان اجتماعي سخي. ويجد هذا المقال أن نظام الضمان الاجتماعي الإلزامي في الدانمرك يوفر حماية ضرورية ضد المخاطر، ولكن تشوبه ثغرات في الحماية مما يطرح تساؤلات بشأن التغطية الفعالة للنظام وكفاية المنافع. Abstract : Será que os "trabalhadores" em plataformas on‐line na Dinamarca são protegidos de maneira eficaz e adequada contra os riscos sociais e do mercado de trabalho? Este artigo debate esta questão fundamental no contexto do mercado de trabalho dinamarquês, conhecido por seus elevados níveis de insegurança no emprego, mas por dispor de um sistema de seguridade social bastante generoso. O artigo conclui que o sistema legal de seguridade social dinamarquês oferece a proteção necessária contra riscos, mas também identifica lacunas na proteção, o que coloca em questão a cobertura efetiva do sistema e a adequação dos benefícios.